COVID-19 pandemic: health impact of staying at home, social distancing and 'lockdown' measures-a systematic review of systematic reviews - Chiesa, Valentina; Antony, Gabriele; Wismar, Matthias; Rechel, Bernd (Journal of public health (Oxford, England), 2021)
To systematically review the evidence published in systematic reviews (SR) on the health impact of staying at home, social distancing and lockdown measures. We followed a systematic review approach, in line with PRISMA guidelines. In October 2020, we searched the databases Cochrane Database of Systematic Reviews, Ovid Medline, Ovid Embase and Web of Science, using a pre-defined search strategy. The literature search yielded an initial list of 2172 records. After screening of titles and abstracts, followed by full-text screening, 51 articles were retained and included in the analysis. All of them referred to the first wave of the coronavirus disease 2019 pandemic. The direct health impact that was covered in the greatest number (25) of SR related to mental health, followed by 13 SR on healthcare delivery and 12 on infection control. The predominant areas of indirect health impacts covered by the included studies relate to the economic and social impacts. Only three articles mentioned the negative impact on education. The focus of SR so far has been uneven, with mental health receiving the most attention. The impact of measures to contain the spread of the virus can be direct and indirect, having both intended and unintended consequences.